Respuestas

2012-07-20T18:15:20+02:00

Pix= 2x2-4x+3                                    Pix+Qix

Qix= 5x3+5x-2                                    Rix-Pix

Rix= -10x2+x-1                                   Pix-Rix

 

-Hallar: Pix + Qix

 

Pix=  0x³+2x² -4x+3

Qix= 5x³ +0x²+5x -2

         5x³ +2x²+ x + 1

.: Pix+Qix= 5x³+2x²+x+1


-Hallar: Rix - Pix:


Rix= -10x² +  x - 1                 Rix= -10x² +  x - 1  

Pix=(    2x² -4x +3)(-1)          Pix= -  2x² + 4x- 3

                                                         -12x²+ 5x- 4

                                               .: Rix-Pix= -12x²+5x-4


-Hallar: Pix - Rix:


Pix=      2x² -4x +3                  Pix=    2x² -4x +3

Rix=(-10x² +  x - 1)(-1)          Rix=  10x² -  x +1

                                                          12x² -5x +4

                                                .:Pix-Rix= 12x²-5x+4


*Espero haberte ayudado, saludos.